Uso de yarrowia lipolytica, para produção de biomassa, utilizando soro de leite como fonte de carbono - Barbosa, Andréia de Fátima Silva (2020)
Whey is the main residue produced by the dairy industry during cheese making. Which as a raw material, can give food technology new potential due to its functional and nutritional properties. Despite having ample potential for use, the serum is still considered an effluent. It is important to develop alternatives to make the use of this agroindustrial waste feasible, because at the same time that the transformation of the serum into new products reduces waste, it can provide gains to the dairy industries. In view of this, during the conduct of this study, the freeze-drying method was used to dehydrate the serum and transform it into powdered serum to facilitate its storage and storage. It was subsequently used as a carbon source for bioconversion by submerged fermentation with five different strains of microorganisms from the Yarrowia lipolytica yeast group, with supplemented mineral medium composed of 1% urea (CH4N2O), 0.1% monobasic potassium phosphate (KH2PO4) and 0.05% magnesium sulfate. The fermentation process was carried out in an incubator with agitation of approximately 80 rpm at a predetermined time interval of 9 days at 30 ° C. The evaluation of the results carried out during each stage of the bioconversion process indicates that the yeast Y. lipolytica QU29 presented a better performance for increasing the whey protein content after the bioprocess, also indicating that it can be used as a carbon source for fermentation, both samples of fresh frozen or lyophilized serum, stored for one year and that even after storage this residue still has potential for use.